Química no ensino fundamental: investigando questões ambientais em uma ilha interdisciplinar de racionalidade - Miletto, Milene Ferreira (2017)
This dissertation aims to report a pedagogical intervention performed in ninth grade Science classes of a public Elementary School. To support this intervention, we based the theoretical ref-erence on Environmental Education, Science Education with Science Technology and Society approaches, Scientific Literacy and Interdisciplinarity areas. This intervention was developed through an Interdisciplinary Island of Rationality (IIR), in which the students started with an analysis of the environmental issues around the neighborhood where the school is located. The students investigated topics that could help answer the previous question of the IIR: What are the relevant problems in our neighborhood and what is the necessary knowledge, especially in the area of chemistry, for understanding and solving social, economic and cultural issues related to the identified problems? These themes correspond to the following black boxes to be opened: soil contamination, garbage, water contamination, basic sanitation, air contamination, contami-nation effects on the human body, and chemical elements. Through these investigation and other activities, the students established relationships between the acquired knowledge and the chemi-cal notions involved (chemical element and periodic table), thus appropriating the contents fore-seen in the curriculum in this stage of teaching. Data on student learning were gathered through recordings of classroom activities, student logbooks, teacher / researcher's diary, interviews with students and collaborating teachers, as well as other productions. The data was examined using the Content Analysis methodology. The results point to the possibilities of learning science through research and knowledge understanding of in an interdisciplinary way. The conclusion comes in order to show that this pedagogical intervention contributed to scientific literacy and the improvement of the students as ecological subjects. Also the evidence shows the potential of pedagogical works involving the environmental and social dimensions for awareness on the role of each student as a citizen in society.